Implementation of the Teaching at the Right Level (TaRL) Approach in Pancasila Education to Strengthen the Character of Discipline and Responsibility at SMAN 1 Nusa Penida, Klungkung Regency - Andryan Andis; Mukhamad Murdiono (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to analyze the implementation of the Teaching at the Right Level (TaRL) approach in Pancasila education to strengthen students’ character of discipline and responsibility at SMAN 1 Nusa Penida. Using a qualitative case study method, data were collected through semi-structured interviews, direct observation, and document analysis. The results indicate that TaRL improves students’ discipline and responsibility by providing structured learning tailored to their understanding levels. However, challenges such as limited diagnostic assessments, inadequate facilities, and low student motivation were found. Supporting factors include a conducive learning environment, active teacher involvement, parental support, flexible policies, and sufficient learning resources. Overall, TaRL is an effective strategy to foster discipline and responsibility in students.